Comparison of beach bacterial water quality indicator measurement methods - Noble, R.T.; Weisberg, S.B.; Leecaster, M.K.; Mcgee, C.D.; Ritter, K.; Walker, K.O.; Vainik, P.M.
Three methods (membrane filtration, multiple tube fermentation, and chromogenic substrate technology kits manufactured by IDEXX Laboratories, Inc.)are routinely used to measure indicator bacteria for beach water quality. To assess comparability of these methods, quantify withinlaboratory variability for each method, and place that variability into context of variability among laboratories using the same method, 22 southern California laboratories participated in a series of intercalibration exercises. Each laboratory processed three to five replicates from thirteen samples, with total coliforms, fecal coliforms or enterococci measured depending on the sample. Results were generally comparable among methods, though membrane filtration appeared to underestimate the other two methods for fecal coliforms, possibly due to clumping. Variability was greatest for the multiple tube fermentation method. For all three methods, within laboratory variability was greater than among laboratories variability.
Keywords: MICROBIOLOGY; INTERCALIBRATION; VARIABILITY; BACTERIAL INDICATORS; BEACH WATER QUALITY